Please Solve this Question if you know and get the brainlyest answer.....
Attachments:
![](https://hi-static.z-dn.net/files/d52/c1f50b8eaf9a02d280bb9e2280917958.jpg)
Answers
Answered by
3
Easy
Step-by-step explanation:
Sum of zeroes=-5
b=(-1)*Sum of zeroes=5
c=product of zeroes=6
so c=6
Polynomial= xsquare + b x +c
= x square + 5x+6
As product of zero is Positive and sum is negative, both the zeroes are negative. They are -2 and -3
Please mark the answer brainliest if it helps
Answered by
18
Answer:
sum of zeros = -5
product of zeros =6
x² - sum of zero X+product of zeros < 0 x ²+ 5 x+6x² + 2 X + 3 X + 6
x (x +2 )+ 3( X + 2 )(X + 2) (X + 3)
x=-2;x=-3
anmol81828:
thnks
Similar questions
Music,
6 months ago
Math,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago